2018
DOI: 10.2147/ceg.s172430
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of catheter-related complications among Japanese patients with central venous catheters as well as patients with short bowel syndrome

Abstract: PurposeShort bowel syndrome (SBS) is a serious rare disorder that is usually managed with parenteral nutrition. Central venous catheter (CVC)-related complications are known to occur, but their incidence rates (IRs) in Japan are unknown. The aim of this study was to estimate the incidence of complications in Japanese patients with CVCs, including patients with SBS using CVCs.Patients and methodsA retrospective cohort study in 64,817 patients with CVCs, including 81 patients with SBS, between April 2008 and Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…30 They also noted that patients who developed SBS as a consequence of malignancy were much older (67.2 years) than noncancer patients with SBS (51.5 years). 30 Thompson et al studied a retrospective cohort of 210 patients with SBS and reported that patients who developed SBS after undergoing bowel resection for intestinal obstruction or mesenteric ischemia were also relatively younger, with a mean age of 48 years. 31 In the current study, we found that almost two-thirds of hospitalizations were >50 years.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…30 They also noted that patients who developed SBS as a consequence of malignancy were much older (67.2 years) than noncancer patients with SBS (51.5 years). 30 Thompson et al studied a retrospective cohort of 210 patients with SBS and reported that patients who developed SBS after undergoing bowel resection for intestinal obstruction or mesenteric ischemia were also relatively younger, with a mean age of 48 years. 31 In the current study, we found that almost two-thirds of hospitalizations were >50 years.…”
Section: Discussionmentioning
confidence: 97%
“…We also noted that more than two-thirds of all hospitalizations were women, which is consistent with a previously estimated higher prevalence of SBS among women. 28,[30][31][32] Nightingale et al pointed out earlier that the reason for the higher prevalence of SBS in women could be attributed to shorter bowel length in women. 33 This sex correlation with bowel length was noted in other recent studies as well; however, they concluded that this correlation was likely due to differences in the heights and weights between the 2 sexes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations